A literature review examining the barriers to the implementation of family witnessed resuscitation in the Emergency Department. (January 2017) - Johnson, Catherine
Highlights: Care provided during death significantly impacts the family's grieving process. All resuscitation efforts can be a successful if healthy grieving is promoted. FWR remains highly controversial and rarely adopted in practice. Numerous professional bodies call for the practice of FWR. FWR can diminish doubt that all was done that could be during resuscitation events. Abstract: Background: Caring for people near death in the Emergency Department (ED) is challenging for professionals, duty bound to respond to the needs of the dying. Family witnessed resuscitation (FWR) is practiced internationally, allowing relatives to be present at the time of a patient's death, offering comfort to the dying and aiding the bereaved along a healthy grief trajectory. Aim: The literature review elicits barriers to the implementation of FWR in the ED, examining why practice is sporadic despite numerous professional bodies calling for implementation. FWR is often met with opposition from staff, subsequently largely dependent upon who is on duty as opposed to adherence with best practice guidelines, risking inconsistent idiosyncratic practice. Findings: Barriers include; a lack of organisational support; shortage of manpower for provision of a family support person; absence of champions for the concept; willful non-adherence due to personal beliefs; restriction on coping strategies reliant upon the ability to emotionally detach, enhancing staff resilience facing repeated exposure to emotionally labile events. Conclusion: All resuscitation efforts can be successful, whether the patient lives or dies, if practice supports healthy grieving. The challenge remains with such divided, entrenched and passionate views, how FWR can be adopted as accepted practice.